Pengambilan Keputusan dalam Manajemen Pendidikan Islam (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
Decision-making constitutes a strategic function in Islamic educational management that determines institutional governance effectiveness, policy quality, and the sustainability of educational implementation. The increasing complexity of the educational environment in the digital era requires decision-making processes that extend beyond managerial rationality by integrating Islamic values as the ethical foundation for institutional policies. Nevertheless, many Islamic educational institutions continue to face significant challenges, including centralized decision-making practices, limited utilization of empirical evidence, and the suboptimal implementation of shūrā (consultative deliberation) principles within managerial processes. This study aims to examine the conceptual framework of decision-making in Islamic educational management through the integration of contemporary management theories and Islamic leadership principles. The study employed a qualitative method using a library research approach. Data were collected from academic books, peer-reviewed scholarly articles, policy documents, and other relevant scientific publications, and were analyzed using content analysis and thematic analysis through the stages of data reduction, categorization, interpretation, and conceptual synthesis. The findings reveal that effective decision-making in Islamic educational management is constructed upon four fundamental dimensions: strategic rationality in policy analysis, the implementation of shūrā through participatory leadership, the strengthening of evidence-based decision-making supported by management information systems, and the orientation toward maṣlaḥah (public benefit) as the primary criterion for evaluating decision quality. These four dimensions collectively establish an adaptive, accountable, data-driven, and collaborative decision-making model that remains firmly grounded in Islamic values. This study contributes conceptually to the advancement of Islamic educational management theory by proposing an integrated decision-making paradigm capable of addressing the challenges of contemporary educational transformation while preserving the ethical and spiritual foundations that distinguish Islamic educational institutions.